Corporate Social Responsibilities, Psychological Contracts and Employee Turnover Intention of SMEs in China - Hui, Zhang (Frontiers in Psychology, 2021)
As an important organizational strategy and action that affects employee perception and attitude, corporate social responsibility is essential for small and medium-sized enterprises (SMEs) to reduce turnover rate and achieve sustainable growth. This paper integrates social identity theory and social exchange theory to construct an external reputation mechanism and internal trust mechanism to explore the influence mechanism of corporate social responsibility on employee turnover intention and the intermediate transmission mechanism of psychological contract. The research results show that corporate social responsibility has a significant negative impact on employee turnover intention. Compared with external corporate social responsibility, internal corporate social responsibility has a stronger negative impact on employee turnover intention; corporate social responsibility has a significant negative impact on employee transactional psychological contract, while corporate social responsibility has a significant positive impact on employee relational psychological contracts; transactional psychological contract has a significant positive effect on employee turnover intention, while relational psychological contract has a significant negative effect on employee turnover intention; psychological contract has a significant and complete mediating effect on the relationship between external corporate social responsibility and employee turnover intention, and the psychological contract plays a significant part of the intermediary role between the internal corporate social responsibility and the employee turnover intention. The conclusions enriches the complex relationship between corporate social responsibility and employee turnover intentions, and provides a reference for SMEs to effectively perform internal and external social responsibilities and reduce employee turnover rates.